PERAN SOCIAL COMMERCE DAN M-COMMERCE TERHADAP PERUBAHAN PERILAKU BELANJA KONSUMEN: Transformasi Digital dan Pergeseran Pola Konsumsi Modern - Difana Safitri; Dewi Asih Nusantari; Amalia Khoerani; Syifa Hasna Afifah; Anjar Sulistyani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Digital developments are driving significant changes in the way people buy and sell. Internet technology, smartphones, and mobile applications have made shopping faster and easier. The emergence of e-commerce, social commerce, and m-commerce has created new, more practical and interactive consumption patterns. This situation has given rise to the need to understand how digital technology influences consumer shopping behavior. The method used in this research is a literature review, which involves data collection by understanding and studying theories from various literature related to this research. Literature review is a type of qualitative research, and this research stage is carried out by compiling both primary and secondary literature sources. Social commerce influences purchases through social interactions, reviews, and influencer content, while m-commerce reinforces these decisions through fast and flexible mobile access. The combination of the two makes the shopping process more instant, personal, and emotional. Easy-to-use mobile technology encourages consumers to make spontaneous decisions, thus forming more dynamic digital shopping patterns. Social commerce and m-commerce play significant roles in shaping modern shopping behavior. Social interactions create trust, while the convenience of mobile applications speeds up transactions. Both encourage faster and more impulsive purchasing decisions. Digital technology is a major factor in changing consumption patterns, making understanding mobile user behavior crucial for businesses and researchers.